Quantitative analysis of NaCl, NaOH, and β-phenylethylamine in water using ultraviolet spectroscopy coupled with partial least squares and net analyte preprocessing - Tang, Xiaojun Tang; Tong, Angxin Tong; Zhang, Feng; Wang, Bin (Penerbit Universiti Kebangsaan Malaysia, 2020)
During the quantitative analysis of NaCl, NaOH, and β-phenylethylamine (PEA) in water samples, the highly overlapped spectra of NaCl, NaOH, and PEA resulted in poor concentration prediction. Meanwhile, the original spectral data of the natural water usually contain noise and interference spectra which will definitely affect the prediction accuracy. Hence, a new quantitative analysis method, which was based on ultraviolet (UV) spectroscopy coupled with partial least squares (PLS) and net analyte preprocessing (NAP), was developed. Firstly, the PLS regression models of the calibration set were constructed by using 15 single component samples, 9 binary component samples and 25 ternary component samples. In addition, the independent test set was built up based on 34 samples to validate the prediction performance of the PLS regression models. The relative errors of prediction (REP) were both less than 3.1% for NaCl, NaOH, and PEA. And the correlation coefficients (Rpred 2 ) of the PLS-1 and PLS-2 models were both not less than 0.98 for NaCl, NaOH, and PEA. Finally, the PLS models coupled with NAP algorithm were successfully used to make the quantitative determination of NaCl, NaOH, and PEA added into the natural water, and the mean recovery rates of NaCl, NaOH, and PEA were satisfactory (95-102%). Therefore, UV spectroscopy coupled with PLS models and NAP algorithm can be considered as an effective method to determine the concentration of NaCl, NaOH and PEA in the natural water